1967
DOI: 10.1063/1.1841169
|View full text |Cite
|
Sign up to set email alerts
|

Infrared Lattice Vibrational Spectra of AgCl, AgBr, and AgI

Abstract: The infrared transmission spectra of AgCl, AgBr, and AgI have been measured between 400–30 cm−1 at room temperature and at 143°K. Strong absorptions characteristic of the transverse optic modes were found, together with weak subsidiary absorptions arising from multiphonon combinations. The longitudinal optic modes of silver chloride and silver bromide were obtained from the reflection spectra of thin, silver halide films deposited on a silvered substrate. Capacitance measurements were used to determine the sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
6
0
3

Year Published

1971
1971
2002
2002

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(11 citation statements)
references
References 34 publications
2
6
0
3
Order By: Relevance
“…6 and 7 it is clear that the static dielectric constant at low temperatures, when space-charge effects are absent, has a value in the range 6 to 8, the precise result at --60~ being 6.8+_0.2. This result agrees well with the value 7-0_+0.3 reported by Bottger and Geddes [26] from measurements on powdered samples at 27~ in the frequency range 10 s to 107 Hz but differs markedly from the results of Sathe et al [27] who give a value of 33.86 from measurements on powder samples under unspecified conditions. Presumably in this latter case space charge effects were present.…”
Section: Resultssupporting
confidence: 90%
“…6 and 7 it is clear that the static dielectric constant at low temperatures, when space-charge effects are absent, has a value in the range 6 to 8, the precise result at --60~ being 6.8+_0.2. This result agrees well with the value 7-0_+0.3 reported by Bottger and Geddes [26] from measurements on powdered samples at 27~ in the frequency range 10 s to 107 Hz but differs markedly from the results of Sathe et al [27] who give a value of 33.86 from measurements on powder samples under unspecified conditions. Presumably in this latter case space charge effects were present.…”
Section: Resultssupporting
confidence: 90%
“…The basic theoretical principles for this structural analysis of thin films can be found in articles published in the 1960's. [10][11][12] It has been amply reported that only transverse vibrational modes can be detected for thin films when the IR absorption spectra are recorded at normal incidence of the radiation. Under these conditions, the electric field vector of the radiation is parallel to the substrate surface.…”
Section: Resultsmentioning
confidence: 99%
“…In particular, it is well known that IR spectra of a film contain information not only on the crystalline structure, but also on the orientation of the crystallographic axes with respect to the film surface. [10][11][12][13] …”
Section: Introductionmentioning
confidence: 99%
“…Fourier transform infrared spectroscopy (FTIR) spectroscopy can be used as a complement of XRD for a more accurate description of the structure of ZrO 2 thin films. Although FTIR is normally used on a ''fingerprint'' basis, a systematic analysis of IR spectra may also provide insight into the ZrO 2 thin film structure [25][26][27][28][29]. Fig.…”
Section: Chemical Compositionmentioning
confidence: 99%